Алгоритм доклинической диагностики сахарного диабета 1-го типа как основа для создания Реестра ДААт-позитивных детей и подростков Украины с прогнозированным развитием заболевания - Tron’ko, M.D.; Zak, K.P.; Popova, V.V. (Ендокринологія | Endokrynologia, 2019)
Aim — The establishment of mechanisms for T1D development at early and late preclinical stages of disease formation in children and adolescents. Material and methods. At the State Institution «V.P. Komisarenko Institute of Endocrinology and Metabolism of NAMS of Ukraine» mentioned the Program «Immunity in the preclinical period of T1D development» was initiated, on the basis of which the Register of marker-positive children with predictable development of type 1 diabetes was created, which includes 612 children aged from 7 to 15 years with burdened heredity, in which the titer of diabetes-associated autobodies (DAA), cytokines, levels of basal and postprandial glycemia and secretion of C-peptide at preclinical and clinical stages of T1D development in children and adolescents based on the performed clinical and immunological study. Results. The new data have been obtained at the State Institution «V.P. Komisarenko Institute of Endocrinology and Metabolism of NAMS of Ukraine», which allowed to substantially supplement the existing ideas about the type 1 diabetes (T1D) pathogenesis. As a result of the performed study, a group of marker-positive children with burdened heredity and a predicted risk of developing the disease was formed. It was found that an increased titer of DAA was observed in 162 (35.45%) of 457 children with burdened heredity with no less than two times determination of DAA presence in them, mainly GADA and IA‑2A, the clinical debut was manifested in 86 (53.08%) of them from 6 months to 16 years (27.4±4.3 months). The formula of combined occurrence and values of simultaneously increased DAA titers to islet autoantigens, namely IA‑2A + GADA, was determined, which is a predictor of both the duration of preclinical stage of T1D development and the debut rate. Impaired cytokine production (increase of the level of proinflammatory cytokines IL‑1α, IL‑6 and TNFα, IL‑8 and IL‑16 while reducing the concentration of IL‑4 in the PB) as key factors of the T1D pathogenesis, which determine the rate of T1D debut, and the aggressiveness of its course were also established. It was found that the early preclinical period of T1D development in DAA+ children was characterized by the presence of dysglycemia in the form of increased glycemia in 2 hour after the glucose tolerance test and a slight decrease in secretion of stimulated C-peptide; in addition, dysglycemia in the form of impaired fasting glycemia was added in DAA+ children in the late preclinical period, and a decrease in both basal and stimulated secretion of the C-peptide was determined, indicating that the potential of pancreatic beta cells was depleted.